STRENGTHENING AKHLAK TASAWUF MATERIAL IN THE SUBJECT OF AKIDAH AKHLAK IN MADRASAH - Rangkuti, Miswar; Hasan, Khairuddin; Nasution, Ahmad Rizki; Monalisa (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
The research aims to explore the process of strengthening akhlak tasawuf material in akidah akhlak subjects in madrasah. The research utilized a library research method involving the stages of collecting, reviewing, and analyzing existing relevant literature pertaining to the topic. The data analysis procedure was conducted by evaluating and synthesizing research data, which could either support or oppose the initial argument. Through conducting a literature synthesis, the researcher compiled a comprehensive picture of the pattern of strengthening akhlak tasawuf, highlighting key findings, and identifying trends that emerged from existing literature. The results of the research show that strengthening akhlak tasawuf in akidah akhlak subjects can be done by adding material on akhlak tasawuf, providing space for students to engage in contemplation in the form of collective remembrance, involving parents to apply akhlak tasawuf values ​​in the family environment and conducting regular evaluations. Providing space for collective remembrance will refine students' feelings in understanding the moral teachings of tasawuf. Contemplation for students will help in correcting wrong morals. Involving parents will strengthen the akhlak tasawuf values ​​that have been instilled. Evaluation is useful for finding out programs that need to be strengthened.